Influence Curent Asset Saving Account (Casa) and Fee- Based Incme ( Fbi ) Against Return On Assets (ROA) at PT. Bank Central Asia, Tbk 2015-2023 period - Sarfika, Pia Eka; Lisiantara , Gregorius Anggana (Jurnal Economic Resource, 2025)
The aim of this research is to analyze the influence of Current Asset Saving Account (CASA) and Fee-Based Income (FBI) on ROA. The research method employs quantitative analysis. The data used are secondary data from the financial statements of PT. Bank BCA. The data analysis technique uses multiple linear regression. The results of the study provide information that the magnitude of ROA possessed by Bank BCA during the period 2015-2023 is significantly determined by the existing CASA and FBI values. When Bank BCA has high CASA and FBI values, it also results in a high ROA value. Conversely, when Bank BCA has low CASA and FBI, it also results in a low ROA for Bank BCA. However, partially, CASA does not determine the magnitude of ROA values of Bank BCA